Perencanaan Sistem Penyaluran Air Limbah Kawasan Aerocity X Wilayah A - Kamila Khalishah; Didin Agustian Permadi; Etih Hartati (Fakultas Teknik, 2019)
Aerocity X is an extended urban area provided to an international airport that consist of integrated business and industrial areas. The total area is 3.480 Ha and it is expected to start construction phase in 2020. This research aims to take consideration of the existing condistions and technical criteria to design a sewerage system at Aerocity X area-zone A which has a total area of 1.801 Ha. The main aim is to provide centralized waste water management facility (including sewerage system) to handle wastewater problems caused by the increase population from the development of this area. The purpose of this research is to calculate dimension of the wastewaster pipeline. There are 43 service blocks and the estimated discharge of wastewater in 2045 in the area is 4,62 m3/s. The results of the calculation of main sewerage diameter is 200-2.350 mm using concrete pipa. The wastewater is conveyed to a Waste Water Treatment Plant (WWTP) located in the area using combination of gravitation and pump